Evaluation of the In vitro Antioxidant and Sensory Properties of Herbal Tea Premix Formulated with Green Tea (Camellia sinensis), Cinnamon (Cinnamomum verum), Ginger (Zingiber officinale), Basil (Ocimum sanctum), Ashwagandha (Withania somnifera), and Jaggery (Saccharum officinarum) - Ganesh J. Bhavsar; Sunakshi Zagade; Tanvi Shinde; Shivani Mule; Yajuvendra Taware; Manas Tadge (Archives of Current Research International, 2025)
This study aimed to develop and evaluate an herbal tea premix formulated with green tea (Camellia sinensis), cinnamon (Cinnamomum verum), ginger (Zingiber officinale), basil (Ocimum sanctum), ashwagandha (Withania somnifera), and jaggery (Saccharum officinarum) for its therapeutic properties and sensory acceptability. Phytochemical analysis revealed that flavonoids (30% in S1) and phenols (25% in S1) were the dominant bioactive compounds, contributing to their strong antioxidant potential. The DPPH radical scavenging activity reached 75.4% at 50 µg/mL in S1, while FRAP (2.8 mmol Fe2+/g) and TPC (82 mg GAE/g) confirmed its high antioxidant activity. The sensory evaluation identified Sample S1 as the most preferred formulation (overall acceptability 8.1) due to its balanced composition and enhanced flavor profile, whereas Sample S4 had the lowest taste acceptability (7.4). Microbial analysis confirmed safety, with no pathogens detected. This nutritionally stable premix holds promise as a functional beverage, but further clinical validation, bioavailability studies, and shelf-life assessment are required for commercialization.